2004
DOI: 10.2337/diabetes.53.4.877
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Insulin in Dogs

Abstract: Pulmonary insulin delivery is being developed as a more acceptable alternative to conventional subcutaneous administration. In 15 healthy Beagle dogs (average weight 9.3 kg), we compared insulin distribution in arterial, deep venous, and hepatic portal circulation. Dogs received 0.36 units/kg s.c. regular human insulin (n ‫؍‬ 6) or 1 mg (2.8 units/kg) or 2 mg (5.6 units/kg) dry-powder human inhaled insulin (n ‫؍‬ 3 and 6, respectively). Postinhalation of inhaled insulin (1 or 2 mg), arterial insulin levels qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Previous studies in dogs have shown that inhaled insulin has a higher and earlier peak of arterial insulin that clears more rapidly than subcutaneous insulin. Despite the similar arterial and hepatic insulin areas under the curve (AUCs) in the two groups, a 20% greater glucose infusion rate was required to maintain euglycemia in the inhaled insulin group relative to the subcutaneous insulin group (2). This finding was consistent with the unique glucose-lowering effect of inhaled insulin seen in human studies.…”
supporting
confidence: 76%
“…Previous studies in dogs have shown that inhaled insulin has a higher and earlier peak of arterial insulin that clears more rapidly than subcutaneous insulin. Despite the similar arterial and hepatic insulin areas under the curve (AUCs) in the two groups, a 20% greater glucose infusion rate was required to maintain euglycemia in the inhaled insulin group relative to the subcutaneous insulin group (2). This finding was consistent with the unique glucose-lowering effect of inhaled insulin seen in human studies.…”
supporting
confidence: 76%
“…Although the reasons for this are not clear, it is possible that 1) the FPG decrease with inhaled insulin relates to IAbs functioning as a repository that slowly releases insulin (22) (however, no correlation between insulin binding and FPG has been observed to date with this preparation) or 2) the inhalation of insulin may increase insulin sensitivity or reduce endogenous glucose release (23,24).…”
Section: Safety and Tolerabilitymentioning
confidence: 93%
“…In a first trial, inhaled insulin as compared with insulin infused in the portal vein increased non-hepatic glucose clearance for up to 3 h [5]. In a second trial, the amount of glucose needed to maintain euglycaemia over 6 h was 20% higher in the inhaled group than in the group that received subcutaneous insulin, despite similar insulin AUCs [6]. In all, it therefore seems unlikely that either basal insulin supplementation or the pharmacodynamic properties of inhaled insulin can account for the difference in fasting glucose noted with the use of inhaled insulin.…”
Section: Abbreviations Fpg: Fasting Plasma Glucosementioning
confidence: 99%
“…The possibility that 'the inhalation of insulin may increase insulin sensitivity or reduce endogenous glucose release' comes from trials in dogs [5,6]. In a first trial, inhaled insulin as compared with insulin infused in the portal vein increased non-hepatic glucose clearance for up to 3 h [5].…”
Section: Abbreviations Fpg: Fasting Plasma Glucosementioning
confidence: 99%